Invasive Sinocerebral Aspergillosis with Optic Nerve Involvement in a Young Immunocompetent Female: A Case Report - Parajiya, Ram; Mahantshetti, Prakash; D, Prem (Journal of Neonatal Surgery, 2025)
We report the case of a 39-year-old immunocompetent female who presented with headache, decreased vision in the left eye, and generalized body weakness. Imaging and histopathology confirmed invasive sino-nasal aspergillosis with extension into the anterior skull base, bilateral frontal lobes, and both optic nerve. She underwent functional endoscopic sinus surgery (FESS) and bifrontal decompressive craniectomy with debulking of abscess along with IV antifungal therapy. This case highlights the aggressive nature of fungal infections even in immunocompetent individuals and the importance of early recognition and multidisciplinary management with aggressive antifungal therapy combined with timely surgical intervention in achieving optimal outcomes.